Edge version of topological degree based indices of Boron triangular nanotubes. Issue 4 (18th May 2020) - Amer, Aamna; Naeem, Muhammad; Rehman, Hamood Ur; Irfan, Muhammad; Saleem, Muhammad Shoaib; Yang, Hong
Abstract: There are many topological indices which have been discussed so far. But the most important topological indices among all these are topological degree-based indices. Topological indices in QSAR/QSPR study helped to check the biological activity and physical aspects of chemical compounds. In this paper, we computed the edge version of some prominent topological degree-based indices like Randić Index, Sum connectivity Index, Zagreb Indices, Atom bond connectivity ABC Index, Harmonic Index and Geometric-arithmetic GA Index of Boron triangular nanotubes.